Identification of a Novel Rice Chromosomal Translocation Line that Could Cause the Heterozygote Semi-Sterility and be Overcome by Genomic Duplication - Ruilian Deng; Hanli You; Qi Ge; Jinwen Wu; Zhukuan Cheng; Lianjun Zhu; Hang Yu; Lin Chen; Muhammad Qasim Shahid; Zijun Lu; Xiangdong Liu (Rice)
Abstract Interspecific and intersubspecific hybrid rice have demonstrated substantial heterosis and increased yield potential, yet they are frequently restricted by complex hybrid sterility (HS). Gene regulation has primarily been used to explain the genetic mechanism of HS; however, it is still unclear how cryptic chromosomal structural hybridity results in heterozygote semi-sterility at the molecular level. This study identified a T-DNA-mediated heterozygous mutant mfss (male and female semi-sterility) in rice, of which the self-pollinated progeny would produce heterozygous semi-sterile mutant plants and homozygous fertile mutant plants, mm, with homozygous in inserted T-DNA. The hybrids derived from mm plants crossing with other rice varieties exhibited conservative semi-sterility. Genomic analyses and fluorescence in situ hybridization (FISH) observation revealed that the end of chromosome 6 (170 genes) translocated with the end of chromosome 2 (566 genes) in mm plants. Among these 736 translocated genes, 102 reproduction-concerned genes, including a new gene, MCM5, were detected, which may result in half of gametes lacking many reproduction-concerned genes to display sterility and caused semi-sterility of mfss-heterozygotes. Hybrids derived from an autotetraploid rice line created from mm plants by genome duplication crossed with a neo-tetraploid rice displayed high fertility, implying that the mfss-heterozygote semi-sterility might be overcome by producing polyploid hybrid rice. These findings elucidate the genetic process of reciprocal translocation causing the heterozygote semi-sterility in rice and offer valuable insights for the production of fertile polyploid hybrid rice.